2014
DOI: 10.1007/978-3-319-02669-5_10
|View full text |Cite
|
Sign up to set email alerts
|

From Grasping to Grooming to Gossip: Innovative Use of Chimpanzee Signals in Novel Environments Supports Both Vocal and Gestural Theories of Language Origins

Abstract: The unique challenges posed by ecologically novel situations can illuminate the limits of flexibility in animal signalling systems. Here we describe the innovative application of species-typical calls by chimpanzees exposed to the novel circumstances in which the animals are dependent upon others to act on the world for them, what we have previously termed "the Referential Problem Space". When chimpanzees are put into the Referential Problem Space, they display attention-getting calls and other auditory signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Studies have demonstrated that some chimpanzees and other great apes voluntarily produce several classes of novel sounds to capture the attention of an otherwise inattentive audience (Theall and Povinelli, 1999;Liebal et al, 2004;Poss et al, 2006;Cartmill and Byrne, 2007;Leavens et al, 2008;Gentry et al, 2015). Experimental evidence has shown that the use of AG sounds is under voluntary control Hopkins et al, 2011), often occurs in conjunction with manual gestures (Hopkins and Cantero, 2003) and grooming (Leavens et al, 2014;Fedurek et al, 2015;Watts, 2016), is lateralized to the left hemisphere (Losin et al, 2008;Wallez et al, 2012), and is socially learned (Taglialatela et al, 2012). For instance, systematic investigations of the production of AG sounds in 279 chimpanzees from two different populations found that 52% and 46% of the chimpanzees within each sample reliably produce some type of AG sound, respectively (Hopkins et al, 2010;Taglialatela et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that some chimpanzees and other great apes voluntarily produce several classes of novel sounds to capture the attention of an otherwise inattentive audience (Theall and Povinelli, 1999;Liebal et al, 2004;Poss et al, 2006;Cartmill and Byrne, 2007;Leavens et al, 2008;Gentry et al, 2015). Experimental evidence has shown that the use of AG sounds is under voluntary control Hopkins et al, 2011), often occurs in conjunction with manual gestures (Hopkins and Cantero, 2003) and grooming (Leavens et al, 2014;Fedurek et al, 2015;Watts, 2016), is lateralized to the left hemisphere (Losin et al, 2008;Wallez et al, 2012), and is socially learned (Taglialatela et al, 2012). For instance, systematic investigations of the production of AG sounds in 279 chimpanzees from two different populations found that 52% and 46% of the chimpanzees within each sample reliably produce some type of AG sound, respectively (Hopkins et al, 2010;Taglialatela et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The long-running debate about the nature of proto-language in our hominid ancestors is addressed in the chapters by Zlatev (2014), See (2014) and Leavens et al (2014), who offer a synthetic solution to the older gestural-versus-vocal origin of language debates by embracing a multimodal approach to the evolution of language. By claiming that communication has, from the very beginning, combined both gestures and vocalizations, they avoid "the greatest unsolved problem for gestural protolanguage theories", as Fitch (2010: 448) puts it: the problem of how gestural protolanguage transitioned into vocal language.…”
Section: Communication: From Social To Symbolicmentioning
confidence: 99%
“…According to Zlatev (2014: 176), speech is a more economic modality to use in bigger groups (for counterarguments see Fitch 2010: 445) and speech is considered to be more symbolic and arbitrary, therefore better suited to "differentiate more clearly between an extensive set of concepts, even when their referents are visually similar." To explain how speech co-evolved with manual signals and eventually became the predominant modality, Leavens et al (2014) interestingly merge Dunbar's from grooming to gossip approach (1996) and Corballis's from hand to mouth approach (2002). According to Corballis, the brains of hominids were prepared for speech production through the long period of controlling intentional manual gestures by the left hemisphere (grooming is usually performed by the right hand).…”
Section: Communication: From Social To Symbolicmentioning
confidence: 99%
See 2 more Smart Citations